2006
DOI: 10.2140/gt.2006.10.2055
|View full text |Cite
|
Sign up to set email alerts
|

Criticality for the Gehring link problem

Abstract: In 1974, Gehring posed the problem of minimizing the length of two linked curves separated by unit distance. This constraint can be viewed as a measure of thickness for links, and the ratio of length over thickness as the ropelength. In this paper we refine Gehring's problem to deal with links in a fixed link-homotopy class: we prove ropelength minimizers exist and introduce a theory of ropelength criticality.Our balance criterion is a set of necessary and sufficient conditions for criticality, based on a stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…As mentioned in the introduction, Cantarella, Fu, Kusner, Sullivan, and Wrinkle [4] have discovered tiny straight segments in a ropelength-critical simple clasp. These segments are a few one-thousands of one unit in length out of a total clasp length of about 6 units (a similar clasp has been constructed by Starostin [20]).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As mentioned in the introduction, Cantarella, Fu, Kusner, Sullivan, and Wrinkle [4] have discovered tiny straight segments in a ropelength-critical simple clasp. These segments are a few one-thousands of one unit in length out of a total clasp length of about 6 units (a similar clasp has been constructed by Starostin [20]).…”
Section: Discussionmentioning
confidence: 94%
“…In the past decade, there has been a great deal of interest in exploring the geometry of tight knots; the definition of thickness has been refined and fully understood [10], it has been shown that C 1,1 minimizers exist in each knot type [5,8,9], some minimizing links have been found [5], and a theory of ropelength criticality has started to emerge [4,21]. The development of this theory has been fueled by a steady stream of numerical data on ropelength minimizers, from Pieranski's original SONO algorithm [15] and Rawdon's TOROS [16], to second-generation efforts such as Smutny and Maddocks' biarc computations [6,19] and the RIDGERUNNER project of Cantarella, Piatek, and Rawdon.…”
Section: Introductionmentioning
confidence: 99%
“…There are many ways to measure the thickness of a space curve, but for links one particularly simple notion, the Gehring thickness, is simply the minimum distance between different components. With Cantarella, Fu and Kusner we introduced a theory of criticality [2] for the Gehring ropelength problem. Our necessary and sufficient conditions for ropelength criticality take the form of a balance criterion which says that the tension force trying to reduce the length of the curves must be balanced by contact forces acting at points achieving the minimum distance.…”
Section: Introductionmentioning
confidence: 99%
“…Our necessary and sufficient conditions for ropelength criticality take the form of a balance criterion which says that the tension force trying to reduce the length of the curves must be balanced by contact forces acting at points achieving the minimum distance. One simple example, with surprising intricacy for its solution [2], is the clasp. This is a generalized link whose components are not closed curves but instead have constrained endpoints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation